Low-carbon-emission high-strength aluminum alloy profile for traffic vehicles and preparation process of low-carbon-emission high-strength aluminum alloy profile

By optimizing the element ratio and process flow in 6082 aluminum alloy, increasing the amount of scrap aluminum added and optimizing the amount of elements such as Mn, Cr, Zr, etc., the problem of insufficient strength and plasticity of existing recycled aluminum alloy profiles is solved, and the preparation of high-performance aluminum alloy profiles is realized to meet the application needs of high-strength mechanical parts.

CN119913405APending Publication Date: 2025-05-02CHONGQING NATIONAL INNOVATION INSTITUTE OF LIGHT ALLOYS CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510335321.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-20
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

When the existing recycled aluminum alloy profiles are added with high scrap aluminum, the plasticity, toughness and strength are significantly reduced, and they cannot meet the application of mechanical parts that have higher strength requirements.

Method used

By optimizing the element ratio in 6082 aluminum alloy, the amount of scrap aluminum added is increased to 58-60%, and the amount of Mn, Cr, Zr and other elements is optimized through combination to collaborate the grain, strengthen and improve corrosion resistance, significantly improve the overall performance of the alloy.

Benefits of technology

With high-performance aluminum alloy profiles with tensile strength of 355MPa, yield strength of 335MPa and elongation of 11% were prepared under high scrap aluminum addition, which satisfies the application needs of high-strength mechanical parts and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005321550120000121
    Figure BDA0005321550120000121
  • Figure BDA0005321550120000131
    Figure BDA0005321550120000131
  • Figure HDA0005321550130000011
    Figure HDA0005321550130000011
Patent Text Reader

Abstract

The invention relates to the technical field of aluminum alloy materials, and discloses a low-carbon-emission high-strength aluminum alloy profile for traffic vehicles and a preparation process thereof.The profile is a 6082 alloy and comprises, by mass, 58%-60% of waste aluminum, 0.7%-1.3% of Si, 0.1%-0.5% of Fe, 0-0.1% of Cu, 0.4%-1% of Mn, 0.6%-1.2% of Mg, 0-0.15% of Cr, 0-0.25% of Zn, 0.02%-0.1% of Ti, 0.02%-0.05% of Zr and the balance aluminum ingots and other impurities. According to the scheme, on the basis of a microalloying strategy, on the premise that 60% of waste aluminum is added, within the 6082 national standard component range, through full-process technological optimization, the performance of the regenerated 6082 aluminum alloy profile reaches the tensile strength of 355 MPa, the yield strength of 335 MPa and the elongation of 11%, and the carbon emission factor of the raw materials is reduced to 10 tCO2e / t or below. The technical problems that under the condition of high Fe content, the number of harmful intermetallic compounds in the regenerated aluminum alloy is large, and the mechanical property is low can be effectively solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of aluminum alloy materials, and in particular to a low-carbon emission and high-strength aluminum alloy profile for transportation vehicles and a preparation process thereof. Background Art

[0002] Cars are one of the most important means of transportation in today's society, and their carbon emissions occupy a significant position in the overall society and transportation fields. The current automotive industry is moving towards energy conservation, emission reduction and safety improvement, and the vehicle lightweight strategy is seen as the key to solving this challenge. Aluminum alloys are widely used in lightweight vehicle design due to their low density, good formability and corrosion resistance. For example, aluminum alloy frame bodies, by adopting a variety of closed-section extrusions, not only reduce the weight of the vehicle body, but also enhance safety. In particular, aluminum alloy anti-collision beams play a significant role in ensuring low-speed collision safety and pedestrian protection, and their application in automotive parts has become mature, especially 6-series aluminum alloy materials and 7-series aluminum alloy materials, which dominate key structural parts such as anti-collision beams and front longitudinal beams.

[0003] In addition, with the release of the Technical Specifications for Passenger Car Life Cycle Carbon Emission Accounting, the carbon emission management of passenger cars throughout their life cycle has been put on the agenda, among which the application of recycled aluminum is regarded as a key means to reduce the carbon emissions of aluminum alloy materials throughout their life cycle. Specifically, the use of recycled aluminum not only greatly reduces resource consumption and environmental pollution, but also saves up to 95% of energy and reduces greenhouse gas emissions by more than 90% in the remelting process compared with the traditional electrolytic aluminum process, with significant economic and environmental benefits. Therefore, many OEMs such as Volvo have clearly put forward the goal of increasing the proportion of recycled materials in order to reduce the carbon footprint of products. At present, the foreign automobile and aluminum processing industries are working closely together to improve the utilization rate of recycled aluminum and develop low-carbon high-performance aluminum alloy materials. Data show that the automotive industry is the main driving force for the consumption of recycled aluminum, and as the trend of lightweighting of automobiles deepens, the demand for recycled aluminum profiles will continue to rise. It is estimated that by 2030, the aluminum consumption per vehicle will reach 350KG, of which recycled aluminum profiles will play an important role.

[0004] However, there are still many problems in the actual application of recycled aluminum in the production of aluminum alloy profiles. Especially when the proportion of scrap aluminum added is high or the grade of scrap aluminum is poor, resulting in the Fe content in the deformed aluminum alloy exceeding 0.3%, Fe is easy to form coarse needle-shaped, lamellar brittle β-type Fe-rich ternary phases. This type of intermetallic compound will serve as a crack source to seriously split the aluminum alloy matrix, resulting in a significant decrease in the plasticity and toughness of the recycled aluminum alloy. A high-strength recycled aluminum alloy profile for automobile anti-collision beams and its preparation process (publication number CN119101836A) developed by the applicant, by optimizing the production process, when producing 6063 alloy profiles, when adding 45-55% scrap aluminum, the yield strength of the prepared profile is maintained at 260-268MPa, the tensile strength is maintained at 281-290MPa, and the elongation is ≥10.5%, which can meet the requirements of recycled aluminum extrusion profiles for automobile anti-collision beams. Although it solves the problem of "the plasticity, toughness and strength of recycled aluminum alloy profiles significantly decreased when a high amount of scrap aluminum is added", the amount of scrap aluminum added and the performance upper limit of the resulting aluminum alloy profiles are still limited and cannot meet higher strength requirements, such as the application of high-strength mechanical parts such as aerospace components and vehicle structural parts.

[0005] In view of this, the development of a low-carbon emission, high-strength aluminum alloy profile and its preparation process for transportation vehicles with higher scrap aluminum addition and better performance can not only effectively make up for the shortcomings of the existing technology, but also further improve the performance of recycled aluminum alloys and broaden their application scenarios. It is of great significance for the production of high-Fe tolerance deformation 6 series / 7 series recycled aluminum alloys suitable for passenger cars, commercial vehicles, rail transit, high-speed rail and other fields. Summary of the invention

[0006] The present invention aims to provide a low-carbon emission, high-strength aluminum alloy profile for transportation vehicles and a preparation process thereof, so as to solve the technical problem that the performance upper limit of the prior art recycled aluminum alloy profile is not high enough and cannot be applied to mechanical parts with higher strength requirements.

[0007] To achieve the above-mentioned purpose, the present invention adopts the following technical scheme: a low-carbon emission and high-strength aluminum alloy profile for transportation vehicles, the profile is 6082 alloy, and includes the following raw materials in mass percentage: 58-60wt% of scrap aluminum, 0.7-1.3wt% of Si, 0.1-0.5wt% of Fe, 0-0.1wt% of Cu, 0.4-1wt% of Mn, 0.6-1.2wt% of Mg, 0-0.15wt% of Cr, 0-0.25wt% of Zn, 0.02-0.1wt% of Ti, 0.02-0.05wt% of Zr, and the remainder is aluminum ingots and impurities with a content of less than 0.05wt%.

[0008] The principles and advantages of this solution are:

[0009] 1. Compared with the existing technology that produces 6063 alloy profiles with a scrap aluminum addition of 45-55%, which is still not high enough, this solution optimizes the ratio of each element in the 6082 alloy, effectively reduces the proportion of β-Fe phase in the harmful aluminum melt, and enables the addition of more recycled aluminum, so that high-strength aluminum alloy profiles can still be prepared when the scrap aluminum addition is increased to 58-60%, effectively taking into account the addition of recycled aluminum and the strength of the profile, meeting the high-strength performance requirements while reducing costs. Specifically, the performance of the 6082 aluminum alloy profile produced by this solution when adding 58-60% scrap aluminum can simultaneously reach a tensile strength of 355MPa, a yield strength of 335MPa, and an elongation of 11%, effectively meeting the requirements of key components in transportation vehicles for recycled aluminum extrusion profiles.

[0010] 2. This solution optimizes the dosage of Mn and Cr in 6082 alloy by combining and optimizing, synergistically refining grains, synergistically strengthening, and improving corrosion resistance, thereby significantly improving the comprehensive performance of the alloy. In addition, the applicant has found through long-term experiments that Mn and Cr elements significantly reduce the harmful β-Fe phase content in aluminum alloys by forming harmless α-Fe phase and AlCrFeSi phase, refining Fe phase, and inhibiting the formation of β-Fe phase. The synergistic effect of the two further enhances this effect, thereby improving the plasticity, toughness, and processing performance of the alloy.

[0011] 3. This scheme significantly improves the tensile strength and yield strength by adding the microalloying element Zr within the composition range allowed by the standard through the combined effects of grain refinement and precipitation strengthening. Specifically, the effects of the Zr element are mainly manifested in the following aspects: (1) Anti-recrystallization performance: The most significant effect of the Zr element is its inhibition of the recrystallization behavior of the alloy. This effect of the Zr element is achieved by forming an Al3Zr (L12 type) intermediate phase. The dispersed Al3Zr particles are small in size and highly dense, and have a strong pinning effect on dislocations and grain boundaries. They can stabilize the substructure of the deformed microstructure and hinder the process of dislocations rearranging into subgrain boundaries and subsequently developing into high-angle grain boundaries during heating, thereby hindering the nucleation of recrystallization. In the process of recrystallization core growth after formation, the Al3Zr particles can hinder the migration of high-angle grain boundaries and inhibit the growth of recrystallization cores, thereby hindering the recrystallization process. (2) Aging behavior: Zr atoms interact closely with vacancies in the initial stage of aging, and vacancies control the migration and diffusion rate of solute atoms, which is extremely critical to the nucleation and growth of GP zones in the early stage of aging. This interaction between Zr and vacancies will change the formation rate and number of GP zones, directly affecting the subsequent aging behavior. (3) Alloy strength: In Zr-containing aluminum alloys, on the one hand, the strengthening phase Al3Zr is dispersed and precipitated during alloy homogenization and hot working, and once precipitated, it is difficult to dissolve again, which has a large dispersion strengthening effect; on the other hand, the alloy is still a non-recrystallized structure after hot working and final heat treatment, and a large number of dislocations and fiber structures generated during deformation are preserved, which has a great deformation strengthening effect. Under the combined effect of these two aspects, the strength of the alloy is significantly improved. In addition, the calculation results of the solidification phase diagram show that adding more than 0.05 Zr will cause Al3Zr particles to precipitate and coarsen before the aluminum liquid, which will cause negative effects. Therefore, the maximum Zr addition in this scheme is 0.05.

[0012] 4. This scheme adopts a cross-system design strategy, using the main alloying element Zn of the 7-series aviation aluminum alloy for the 6-series alloy composition, introducing additional precipitation structure, and further improving the alloy strength. By adding an appropriate amount of Cu element to the 6-series aluminum alloy, not only can the plasticity during hot working be significantly improved, but also the heat treatment strengthening effect is increased. The reason is that the presence of Cu element can reduce the precipitation time of the precipitation phase, reduce the precipitation temperature, and increase the number of precipitation phases, thereby improving the alloy performance. In addition, the Ti element generally exists in the form of A l3 Ti crystalline phase can prevent grain growth and hinder atomic diffusion to a certain extent, so it is often used as a refiner.

[0013] Preferably, as an improvement, the Mg content is 0.7-1.0 wt%, and the Si content is 0.9-1.15 wt%.

[0014] Technical effect: This scheme adopts the above-mentioned setting to optimize the alloy performance. Specifically, the alloy strength is proportional to the content of Mg2Si phase in the matrix. The increase in the total amount of Mg+Si atoms can accelerate the hardening rate of Al-Mg-Si alloy during the aging process, and the improvement of mechanical properties after aging will also increase. The applicant found through experiments that under different total amounts of Mg+Si, the Mg / Si mass ratio that is most conducive to the formation of nanoclusters is 1. In the 6082 aluminum alloy standard, the range of Mg element content is 0.6-1.2wt%, the range of Si element content is 0.7-1.3wt%, and the maximum value of the total Mg+Si content just reaches 2.5wt%. In order to ensure that the strength meets the standard, as many Mg2Si phases as possible should be present in the alloy. Therefore, the content of Mg element is preferably 0.8-0.9wt%; considering that the balance ratio of Mg and Si elements is 1.73, and the beneficial effect of a small amount of excess Si on the alloy performance, the content of Si element is preferably 0.7-1.0wt%, which effectively improves the alloy performance.

[0015] Preferably, as an improvement, the Mn content is 0.6-0.65wt%, and the total amount of Mn element and Cr element is 0.7-0.8wt%.

[0016] Technical effect: This scheme adopts the above-mentioned settings to optimize the synergy of elements, balance performance and control costs. Specifically, Mn can inhibit recrystallization and control the particle size in the subsequent formation process, which can improve strength, corrosion resistance, impact toughness and bending properties. Cr and Mn have similar effects. At the same time, Cr can also inhibit the precipitation of Mg2Si phase at the grain boundary, delay the natural aging process, and improve the strength after artificial aging. Cr can also refine the grains, making the grains after recrystallization slender, thereby improving the corrosion resistance of the alloy. Furthermore, during the homogenization treatment, both Mn and Cr can promote the transformation of β-Fe phase into α-Fe phase. In the solid solution process, the presence of Mn and Cr elements can hinder the occurrence of recrystallization and prevent grain growth. The promotion effect of adding these two elements at the same time will be superimposed. However, the applicant has found through long-term experiments that if the Mn content is too high, a coarse second phase containing Mn is easily formed, and the Mn element often exists in the form of combining with the Si element to form an AlMnSi phase (the effect of improving the alloy strength is smaller than that of the Mg2Si phase). When the Mn content is high, more Si elements will be consumed to form the AlMnSi phase, resulting in a decrease in the Si element used to form the Mg2Si phase, thereby reducing the strength of the alloy; at the same time, the Mn element is prone to severe intracrystalline segregation in the aluminum matrix, resulting in a coarse-grained structure of the extruded profile, reducing the oxidation coloring effect of the profile.

[0017] Preferably, as an improvement, the 6082 alloy profile has a tensile strength of ≥320 MPa, a yield strength of ≥300 MPa, and an elongation of ≥8%.

[0018] Technical effect: This scheme adopts the above-mentioned settings to significantly improve the comprehensive mechanical properties of 6082 alloy. Its high strength, good plasticity and excellent comprehensive performance make it suitable for high-demand occasions in many fields such as transportation, construction, machinery manufacturing, aerospace, etc.

[0019] Preferably, as an improvement, the present solution also provides a process for preparing a low-carbon emission high-strength aluminum alloy profile for a transportation vehicle, comprising the following steps:

[0020] Step 1: Prepare the raw materials: prepare the raw materials according to the above ratio;

[0021] Step 2, melting and casting treatment: the raw materials prepared above are put into a smelting furnace, the raw materials are melted in the smelting furnace, the alloy composition is adjusted, the high-purity argon gas in the furnace is refined without flux, and the raw materials are left to stand, and the double-rotor degassing furnace outside the furnace is degassed, and the 50ppi single-stage plate filter is purified, and the purified aluminum melt is cast into a recycled aluminum ingot by a semi-continuous casting equipment;

[0022] Step 3: homogenization treatment: subjecting the ingot obtained in step 2 to a two-stage homogenization treatment to obtain an ingot;

[0023] Step 4: extrusion treatment: extruding the ingot obtained in step 3 to obtain a profile;

[0024] Step 5: straightening the profile obtained in step 4;

[0025] Step 6: Solution treatment: subject the profile obtained in step 5 to solution treatment, and then perform water quenching;

[0026] Step 7: Aging treatment: The profile obtained in step 6 is subjected to aging treatment to obtain a finished profile.

[0027] Technical effect: This scheme adopts the above-mentioned setting, which is convenient for taking into account the increase in the amount of scrap aluminum added in the raw materials and the performance of the profiles, while effectively shortening the production cycle and improving the production efficiency of the profiles. Specifically, the present invention uses a double-rotor degassing furnace to degas the aluminum melt, and effectively utilizes the high-speed centrifugal shearing iron removal technology of aluminum liquid, overcomes the gravity field and temperature field effects in the melt, and obtains an excellent purification effect, effectively reducing the harmful β-Fe phase content in the aluminum melt, reducing the degree of reduction in profile performance caused by high scrap aluminum addition, and increasing the amount of scrap aluminum added in the 6082 profile raw materials. Further improve the utilization rate of recycled aluminum, and provide technical support for making full use of recycled aluminum to prepare high-strength profiles. And by combining and optimizing the process steps, the harmful β-Fe phase content in the profile can be effectively and quickly reduced, shortening the overall production time and improving production efficiency.

[0028] Preferably, as an improvement, in step three, the two-stage homogenization treatment includes: primary homogenization, controlling the heating temperature to 440-460°C, and the insulation time to 4-6 hours; secondary homogenization, controlling the heating temperature to 550-570°C, and the insulation time to 13-17 hours.

[0029] Technical effect: This scheme adopts the above settings to significantly improve the comprehensive performance of 6082 alloy profiles. Specifically, the heating temperature is controlled to be 440-460℃ and the holding time is 4-6h during the first-level homogenization treatment, which effectively eliminates the segregation of the alloy ingot during the casting process and makes the alloy elements initially evenly distributed. It can also promote the dispersion and precipitation of Al3Zr (L12) while avoiding the formation of coarse incoherent Al3Zr (DO23). During the second-level homogenization treatment, the heating temperature is controlled to be 550-570℃ and the holding time is 13-17h. The higher temperature promotes the diffusion of low diffusion coefficient elements and dissolves the residual primary Mg2Si phase (Mn, Fe phase). Compared with the 20-24h holding treatment required for the second-level homogenization treatment during the preparation of 6063 alloy, this scheme effectively shortens the second-level homogenization treatment time by 7h, significantly improving production efficiency. The applicant has found through long-term experiments that if the heating temperature is too low during the primary homogenization treatment, the segregation will not be fully eliminated, the alloy elements will be unevenly distributed, and Al3Zr (L12) type particles cannot be effectively formed; if the heating temperature is too high, coarse and incoherent Al3Zr (DO23) particles will be easily formed, and the modification effect of Zr cannot be exerted. If the heating temperature is too low or the time is too short during the secondary homogenization treatment, the residual primary phase is difficult to dissolve back, and the Fe-containing phase is difficult to thin, melt and spheroidize; if the heating temperature is too high or the time is too long, not only will the production cost increase, but the grains will coarsen rapidly, causing the toughness of the alloy to drop sharply and the corrosion resistance to deteriorate. In severe cases, it may also lead to overburning, causing the alloy performance to deteriorate rapidly.

[0030] Preferably, as an improvement, in step four, the extrusion process is to heat the ingot to a temperature of 490-530°C, a mold temperature of 460-500°C, an extrusion barrel temperature of 430-470°C, and an extrusion speed of 1-3 mm / s to obtain a profile.

[0031] Technical effect: This scheme adopts the above settings to facilitate the efficient and high-quality production of 6082 alloy profiles with excellent performance. Specifically, the heating temperature of the ingot is controlled at 490-530°C, the plasticity of the alloy is significantly improved, and the ingot can be more easily plastically deformed during the extrusion process, so that it can be smoothly processed into the required profile shape. At the same time, the appropriate temperature can also reduce the generation of internal stress and ensure the stability of the internal structure of the profile. Controlling the mold temperature at 460-500°C can ensure that the temperature difference between the mold and the ingot is within a reasonable range, so that the metal can evenly fill the mold cavity during the extrusion process, which is conducive to obtaining profiles with high dimensional accuracy and good surface quality. In addition, the appropriate mold temperature can also extend the service life of the mold and reduce production costs. Setting the extrusion barrel temperature to 430-470°C can maintain the fluidity of the metal during the extrusion process, avoid poor metal flow due to too low temperature, and produce extrusion defects such as surface cracks and folds; at the same time, it also prevents overheating and overburning of the metal structure caused by excessively high temperature, and ensures the mechanical properties of the profile. By controlling the extrusion speed at 1-3 mm / s, the moderate speed can make the metal fully deformed during the extrusion process, ensure the uniform internal structure of the profile, avoid uneven deformation of the metal due to too fast speed, and cause stress concentration and structural defects in the profile; while too slow speed will reduce production efficiency and increase production costs. And the applicant has found through long-term experiments that if the ingot heating temperature is too low, it will lead to insufficient plasticity of the metal, and a greater extrusion force is required during the extrusion process, which is easy to cause excessive equipment load, and the profile is prone to defects such as cracks and uneven deformation; if the heating temperature is too high, the alloy structure may be overheated and overburned, reducing the strength and toughness of the profile. If the mold temperature is too low, it is difficult for the metal to fill the mold cavity, and defects such as cold shut and undercasting are prone to occur on the surface of the profile, affecting the dimensional accuracy and surface quality of the profile; if the mold temperature is too high, the thermal fatigue of the mold is aggravated, the service life is shortened, and the profile may stick to the mold, affecting production efficiency and product quality. If the temperature of the extrusion barrel is too low, the metal fluidity is poor, extrusion defects are likely to occur, and the extrusion force will increase; if the temperature of the extrusion barrel is too high, the metal structure will overheat, reducing the performance of the profile. If the extrusion speed is too slow, the production efficiency will be low and the cost will increase; if the extrusion speed is too fast, the metal deformation will be uneven, internal defects will easily occur, and the mechanical properties of the profile will be reduced.

[0032] Preferably, as an improvement, in step six, the solution treatment is carried out at a temperature of 545 to 565° C. for 30 to 60 minutes.

[0033] Technical effect: This scheme adopts the above-mentioned setting to effectively improve the comprehensive mechanical properties of 6082 alloy profiles, so that it can better meet the needs of various application scenarios. Specifically, from a microscopic point of view, after the solution treatment forms a uniform solid solution, the atomic arrangement inside the alloy is more regular, the degree of lattice distortion is reduced, and dislocation movement is easier. In the subsequent aging treatment, the evenly distributed solute atoms will serve as the core to promote the uniform and fine precipitation of the strengthening phase, greatly improving the strength and hardness of the alloy. From the perspective of macroscopic performance, suitable solution treatment can effectively improve the comprehensive mechanical properties of 6082 alloy profiles, so that it can better meet the needs of various application scenarios. And the applicant has found through long-term experiments that if the insulation temperature is too low, the strengthening phase in the alloy cannot be fully dissolved, and the strengthening phase is unevenly precipitated during the subsequent aging treatment, resulting in insufficient strength and hardness of the alloy, which cannot meet the use requirements. If the insulation temperature is too high, the grains will grow rapidly, the toughness and plasticity of the alloy will be greatly reduced, and brittle fracture is prone to occur when subjected to force. If the holding time is too short, the strengthening phase will not be completely dissolved, the solid solution strengthening effect will be poor, and the comprehensive mechanical properties of the alloy will be difficult to improve. If the holding time is too long, it will not only increase production costs, but may also cause overburning, deteriorate alloy properties, and reduce product quality.

[0034] Preferably, as an improvement, in step seven, the aging treatment is to transfer the profile obtained by water quenching to a temperature of 160-180° C. within 3 hours and keep it warm for 7-9 hours.

[0035] Technical effect: This scheme adopts the above-mentioned setting. After water quenching, the alloy is in a metastable state, and the solute atoms have not significantly aggregated and precipitated in a short time. Timely transfer for aging treatment can ensure that the solute atoms begin to precipitate in an orderly manner at the right time, thereby forming an effective strengthening phase and improving performance. In this scheme, the temperature can ensure that the strengthening phase is uniformly, finely and dispersedly precipitated, effectively improving the strength, hardness and wear resistance of the alloy while maintaining a certain toughness. The applicant found through long-term experiments that if the transfer time exceeds 3h, the solute atoms in the alloy will naturally aggregate and precipitate during the parking process, resulting in the limited improvement of the strength and hardness of the alloy during the subsequent aging treatment, and the mechanical properties cannot meet expectations. If the aging temperature is too low, the solute atoms diffuse slowly, the amount of strengthening phase precipitation is small and the size is small, the strengthening effect of the alloy is not good, and it cannot meet the strength requirements in actual use. If the aging temperature is too high, the strengthening phase grows too fast, and it is easy to coarsen, resulting in a decrease in the strength and toughness of the alloy, and brittle fracture is easy to occur when subjected to force. If the holding time is too short, the strengthening phase cannot be fully precipitated, and the strength and hardness of the alloy are insufficiently improved; if the holding time is too long, the strengthening phase grows excessively and coarsens, which not only fails to improve the alloy performance, but reduces the toughness and plasticity of the alloy, and the production cost will increase accordingly.

[0036] The principles and advantages of this solution:

[0037] 1. This scheme is based on the microalloying strategy. By adding more Mn elements in combination, it helps to promote the transformation of β-iron phase into α-iron phase, and further reduce the influence of Fe in scrap aluminum on the alloy. And based on the premise of 60% scrap aluminum addition ratio, within the scope of 6082 national standard composition, through the optimization of the whole process, the recycled 6082 aluminum alloy profiles can simultaneously achieve high performance of tensile strength of 355MPa, yield strength of 335MPa, and elongation of 11%; and the carbon emission factor of raw materials is reduced to below 10tCO2e / t. It effectively solves the technical problems of excessive harmful intermetallic compounds and low mechanical properties in recycled aluminum alloys under high Fe content conditions, thereby ensuring that recycled aluminum profiles have stable and suitable service performance, and provides a new solution for effectively reducing carbon emissions and reducing costs throughout the life cycle of the vehicle.

[0038] 2. This solution effectively refines and degasses during the melting and casting stage, reduces the β-Fe phase content, and improves the performance of the profile. This solution optimizes the raw material ratio, manually sorts the extrusion waste (extrusion residue, hot peeling material, extrusion profile scraps, etc.), uses a handheld spectrometer to pick and sort, and uses aluminum liquid high-speed centrifugal shearing iron removal technology (melting furnace high-purity argon refining + degassing furnace double rotor solvent-free refining and degassing + 50ppi single-stage plate online filtration) and other operations to effectively achieve melt purification and degassing effects, reduce the β-Fe phase content generated by the raw materials during the smelting process, and thus improve the performance of the profile.

[0039] 3. This solution further reduces the β-Fe phase content and improves the performance of the profile by reasonably optimizing the homogenization temperature and time during the homogenization stage. This solution observes the thickness of the Fe-containing phase, uses a calculation formula based on diffusion theory, and corrects the secondary soaking temperature and time to ensure that more than 80% of the needle-like β-Fe phase is effectively thinned and melted, and is converted into Chinese character / skeletal or spherical α-Fe phase as much as possible, reducing the probability of it becoming a crack source and causing rapid crack expansion. Compared with the 6063 alloy, the soaking time can be shortened by about 7 hours, which is more conducive to the rapid production of the alloy.

[0040] 4. This solution optimizes parameters during the extrusion stage, effectively handles the remaining β-Fe phase content, and improves the performance of the profile. This solution controls key deformation process parameters such as ingot heating temperature, extrusion speed, and deformation amount to effectively crush and rotate the relatively coarse needle-like β-Fe phase remaining after equalization during the thermal deformation process, further reducing the possibility of it cutting the matrix and improving the strength performance of the profile.

[0041] 5. This solution optimizes parameters during the heat treatment stage to compensate for the performance loss caused by high scrap aluminum addition and improve profile performance. Under the premise of reasonable proportion of alloy elements, especially Mg / Si, this solution uses optimized solid solution and aging processes to maximize the mechanical properties of 6082 and 6063 alloys and compensate for the performance loss caused by the introduction of harmful β-Fe phase due to the addition of recycled aluminum. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 This is a performance comparison chart of the low-carbon emission and high-strength aluminum alloy profile for transportation vehicles in Example 10 of the present invention and the common 6 series alloy profiles on the market.

[0043] Figure 2 This is a performance comparison chart of the low-carbon emission and high-strength aluminum alloy profile for transportation vehicles in Example 10 of the present invention and the common 7 series alloy profiles on the market.

[0044] Figure 3 The solidification phase diagram calculation results of the alloys obtained by adding different amounts of Zr in Example 10 of the present invention and Comparative Example 7 are shown. DETAILED DESCRIPTION

[0045] The present invention is further described in detail below in conjunction with examples, but the embodiments of the present invention are not limited thereto. Unless otherwise specified, the technical means used in the following examples and experimental examples are conventional means well known to those skilled in the art, and the materials, reagents, etc. used can be obtained from commercial sources.

[0046] Program Overview

[0047] The present invention provides a low-carbon emission high-strength aluminum alloy profile for transportation vehicles, the profile is 6082 alloy, including the following raw materials: 58-60wt% of scrap aluminum, 0.6%-0.65wt% of Mn, 0-0.15wt% of Cr, 0.8-0.9wt% of Mg, 0.7-1.0wt% of Si, 0-0.2wt% of Zn, 0-0.1wt% of Ti, 0.02-0.05wt% of Zr, 0-0.5wt% of Fe, 0-0.1wt% of Cu, and the remainder is aluminum ingot and impurities with a content of less than 0.05wt%. Among them, the total amount of (Mn+Cr) is 0.70-0.80wt%. The tensile strength of the prepared 6082 alloy profile is ≥350MPa, the yield strength is ≥330MPa, and the elongation is ≥11%.

[0048] The present invention also provides a process for preparing a low-carbon emission high-strength aluminum alloy profile for a transportation vehicle, comprising the following steps:

[0049] Step 1: Prepare the raw materials: prepare the raw materials according to the above ratio; specifically, the scrap aluminum includes 1 series and 6 series aluminum alloy extrusion residues, hot stripping materials, extruded profile scraps and other conventional social recycled waste.

[0050] Step 2: Melting and casting: The raw materials prepared above are put into the melting furnace, melted in the melting furnace, the alloy composition is adjusted, and the high-purity argon gas in the furnace is refined without flux for 30 to 60 minutes, and then allowed to stand for 30 to 120 minutes. Then, high-purity argon gas is introduced, the working pressure of the degasser is 0.3 to 0.5 MPa, and the gas flow rate is 1.5 to 3.5 m 3 / h, the rotor speed is 250-450r / min, and the aluminum melt is degassed in a double-rotor degassing furnace outside the furnace, and after purification by 50ppi single-stage plate filtration, the purified aluminum melt is cast into a recycled aluminum ingot using a semi-continuous casting device;

[0051] Step 3, homogenization treatment: the ingot obtained in step 2 is subjected to two-stage homogenization treatment to obtain an ingot; wherein, in the first stage of homogenization, the heating rate is controlled at 60-80°C / h, the temperature is raised to 440-460°C, and then kept warm for 4-6h; in the second stage of homogenization, the heating rate is controlled at 20-30°C / h, the temperature is heated to 550-570°C, and then kept warm for 13-17h.

[0052] Step 4: extrusion treatment: extruding the ingot obtained in step 3 at a heating temperature of 490-530° C., a mold temperature of 460-500° C., an extrusion barrel temperature of 430-470° C., and an extrusion speed of 1-3 mm / s to obtain a profile;

[0053] Step 5, straightening treatment, straightening the profile obtained in step 4, wherein the deformation amount of the profile during the straightening treatment is 1.5-3%, and the profile is obtained;

[0054] Step 6: Solution treatment: The profile obtained in step 5 is subjected to solution treatment at 545-565°C for 30-60 minutes, and then water quenched;

[0055] Step 7: Aging treatment: The profile obtained in step 6 is transferred to a temperature of 160-180° C. within 3 hours and kept at this temperature for 7-9 hours for aging treatment to obtain a finished profile.

[0056] Example 1

[0057] The present invention provides a low-carbon emission high-strength aluminum alloy profile for transportation vehicles, the profile is 6082 alloy, including the following raw materials: 60wt% of scrap aluminum, 0.65wt% of Mn, 0.05wt% of Cr, 0.9wt% of Mg, 1.0wt% of Si, 0.15wt% of Zn, 0.06wt% of Ti, 0.05wt% of Zr, 0.5wt% of Fe, 0.1wt% of Cu, and the remainder is aluminum ingots and impurities with a content of less than 0.05wt%. Among them, the total amount of (Mn+Cr) is 0.7wt%.

[0058] The present invention also provides a process for preparing a low-carbon emission high-strength aluminum alloy profile for a transportation vehicle, comprising the following steps:

[0059] Step 1: Prepare the raw materials: prepare the raw materials according to the above ratio;

[0060] Step 2: Melting and casting: The raw materials prepared above are put into the melting furnace, melted in the melting furnace, the alloy composition is adjusted, and the high-purity argon gas in the furnace is refined without flux for 45 minutes, and then left to stand for 60 minutes. 3 / h, rotor speed of 400r / min, degassing in a double-rotor degassing furnace outside the furnace, and 50ppi single-stage plate filtration purification, and then using semi-continuous casting equipment to cast the purified aluminum melt into recycled aluminum ingots;

[0061] Step 3, homogenization treatment: the ingot obtained in step 2 is subjected to two-stage homogenization treatment to obtain an ingot; wherein, in the first stage of homogenization, the heating rate is controlled to be 70°C / h, the temperature is raised to 4°C, and then kept warm for 5h; in the second stage of homogenization, the heating rate is controlled to be 25°C / h, the temperature is heated to 560°C, and then kept warm for 15h.

[0062] Step 4: extrusion treatment: the ingot obtained in step 3 is extruded under the conditions of a heating temperature of 510° C., a mold temperature of 480° C., an extrusion barrel temperature of 450° C., and an extrusion speed of 2 mm / s to obtain a profile;

[0063] Step 5, straightening treatment, straightening the profile obtained in step 4, the deformation amount of the profile during the straightening treatment is 2%, and the profile is obtained;

[0064] Step 6: Solution treatment: The profile obtained in step 5 is subjected to solution treatment at 555°C for 45 minutes, and then water quenched;

[0065] Step 7: Aging treatment: The profile obtained in step 6 is transferred to 170° C. within 2 hours and kept at this temperature for 8 hours for aging treatment to obtain a finished profile.

[0066] Example 2

[0067] This embodiment is basically the same as Embodiment 1, except that the secondary homogenization temperature is 550° C. and the time is 13 h.

[0068] Example 3

[0069] This embodiment is basically the same as Embodiment 1, except that the extrusion speed is 3 mm / s.

[0070] Example 4

[0071] This embodiment is basically the same as Embodiment 1, except that the heating temperature of the extrusion ingot is 490°C.

[0072] Example 5

[0073] This embodiment is basically the same as embodiment 1, except that the transfer time after extrusion is 3 hours.

[0074] Example 6

[0075] This embodiment is basically the same as embodiment 1, except that the aging treatment is performed at 180° C. for 8 h.

[0076] Example 7

[0077] This embodiment is basically the same as Embodiment 1, except that the solution temperature is 545°C.

[0078] Example 8

[0079] This embodiment is basically the same as Embodiment 1, except that a two-stage solid solution is adopted.

[0080] Example 9

[0081] This embodiment is basically the same as Embodiment 1, except that the aging treatment temperature is 160° C. and the aging treatment time is 9 hours.

[0082] Example 10

[0083] This embodiment is basically the same as Embodiment 1, except that the aging treatment is performed at 170° C. for 8 h, and the Fe content in the alloy is 0.35 wt %.

[0084] Embodiment 11

[0085] This embodiment is basically the same as Embodiment 1, except that a small-scale test is carried out in a laboratory, and the experimental small-scale test uses an Al-Fe intermediate alloy to simulate the cumulative effect of the Fe element introduced by adding real recycled aluminum.

[0086] Comparative Example 1

[0087] This embodiment is basically the same as Embodiment 1, except that the standing time in the furnace is 150 minutes.

[0088] In this comparative example, since the static time in the furnace was too long, cracks occurred at the inclusions during extrusion.

[0089] Comparative Example 2

[0090] This embodiment is basically the same as Embodiment 1, except that the rotor speed of the degasser is 200 r / min.

[0091] In this comparative example, due to the insufficient number of rotors of the degasser, the hydrogen content of the melt was high, resulting in a high hydrogen content in the ingot and cracking during extrusion.

[0092] Comparative Example 3

[0093] This embodiment is basically the same as the embodiment 1, except that 40ppi single-stage plate filtration is used again.

[0094] In this comparative example, the plate filtering accuracy is low, resulting in inclusions in the ingot and cracking at the inclusions during extrusion.

[0095] Comparative Example 4

[0096] This embodiment is basically the same as Embodiment 1, except that the secondary homogenization temperature is 530°C.

[0097] In this comparative example, the secondary homogenization temperature is too low, resulting in that the Fe in the alloy cannot be sufficiently thinned and melted, thereby causing the strength of the alloy to be low.

[0098] Comparative Example 5

[0099] This embodiment is basically the same as Embodiment 1, except that the secondary homogenization time is 11 hours.

[0100] In this comparative example, the secondary homogenization time is insufficient, resulting in the failure of the Fe content in the alloy to be sufficiently thinned and melted, thereby causing the strength of the alloy to be low.

[0101] Comparative Example 6

[0102] This embodiment is basically the same as embodiment 1, except that the profile obtained in step 6 is transferred within 4 to 5 hours.

[0103] In this comparative example, the transfer time is too long, and the profile is adversely affected by natural aging to a certain extent during the storage period, and the strength after aging treatment is low.

[0104] Comparative Example 7

[0105] This embodiment is basically the same as the embodiment 1, except that the added amount of Zr element is 0.12 wt %.

[0106] In this comparative example, due to excessive addition of Zr element, Al3Zr particles precipitate and coarsen before the aluminum liquid, which reduces the alloy performance and causes negative effects.

[0107] Experimental Example 1: Performance Testing

[0108] The 6082 alloy profiles prepared in the above Examples 1 to 10 and Comparative Examples 1 to 7 were tested with reference to standards GB / T228.1-2021, GB / T5027-2016, and GB / T5028-2008. The results are shown in Table 1.

[0109] Table 1 Data results in Examples 1 to 10 and Comparative Examples 1 to 7

[0110]

[0111]

[0112] Experimental data analysis shows that this scheme effectively increases the amount of scrap aluminum added in the raw materials by combining and optimizing the raw material composition, process steps and parameters, and the scrap aluminum in the scheme (alloy production pilot) is not limited to the use of 6082 scrap. Compared with an aluminum alloy material and its preparation method and an automotive high-strength seamless pipe (publication number CN118166243A) in the prior art, which adopt the same type of recycling strategy (because it only uses 6082 scrap, and the addition amount is unknown, and no harmful Fe phase is formed, the processing difficulty is greatly reduced, and a short-term homogenization and insulation for 7 to 9 hours can meet the requirements), this scheme has higher scrap aluminum compatibility and a wider source of scrap aluminum. It can still effectively improve the alloy performance to achieve high performance of tensile strength of 355MPa, yield strength of 335MPa, and elongation of 11% at the same time, and the carbon emission factor of raw materials is reduced to below 10tCO2e / t, which significantly broadens the application scenarios of 6082 alloy profiles, reduces raw material costs, improves production efficiency, and achieves the unity of resources, environmental protection, and benefits.

[0113] The applicant has found through long-term experiments that the Fe content, the standing time in the furnace, the number of rotors of the degasser, the secondary homogenization temperature and time, the extrusion treatment, the aging treatment, the solution treatment and other stages or parameters will affect the performance of the 6082 alloy profiles finally prepared. Specifically, even if the Fe content in Example 1 reaches the upper limit of 0.5wt.%, the tensile strength of the 6082 alloy profile obtained is reduced, but it is still as high as 343MPa, and the yield strength is as high as 327MPa, and the elongation is as high as 13%, which effectively meets the use requirements of the 6082 alloy profiles. In Example 2, although the secondary homogenization temperature and time are both at the minimum limit, the tensile strength and yield strength of the prepared 6082 alloy profile are reduced to >300, and the elongation is as low as 9%, which is a decrease as a whole, but it is still higher than the performance strength of conventional 6082 alloy profiles (reference standard GB / T 6892-2023 Chinese standard name: General industrial aluminum and aluminum alloy extruded profiles, 6082 alloy profile performance requirements are tensile strength 290MPa, yield strength 250MPa, elongation 6% (wall thickness ≤5mm)).

[0114] If the standing time in the furnace is too long (such as Comparative Example 1), the alloy will crack at the inclusions when it is extruded; if the number of rotors of the degasser is insufficient (Comparative Example 2), the hydrogen content of the melt will be high, resulting in a high hydrogen content in the ingot, which will cause cracking during extrusion. If the plate filtration accuracy is low (such as Comparative Example 3), inclusions will be present in the ingot, causing cracking at the inclusions during extrusion. If the secondary homogenization temperature is too low or the secondary homogenization time is insufficient (such as Comparative Examples 4 and 5), it will cause the residual primary phase to be difficult to dissolve back, and the Fe-containing phase will be difficult to thin, melt and spheroidize, resulting in low strength of the alloy. If the transfer time is too long (such as Comparative Example 6), the profile will be adversely affected by a certain degree of natural aging during the parking period, and the strength will be low after aging treatment.

[0115] Figure 1 and Figure 2 The performance comparison chart of the 6082 alloy profile prepared in Example 10 of this solution and some 6 series / 7 series alloys in the existing market is shown. It shows that the 6082 alloy profile prepared in this solution has higher performance. Even if they are both 6082 alloy profiles, the performance of the 6082 profile obtained by adding 60% scrap aluminum in this solution is higher than that of Citroen 6082, which shows that this solution effectively solves the technical problems of excessive harmful intermetallic compounds and low mechanical properties in recycled aluminum alloys under high Fe content conditions, thereby ensuring that the recycled aluminum profile has stable and appropriate service performance, and provides a new solution for effectively reducing carbon emissions and reducing costs throughout the life cycle of the vehicle. Figure 3The calculation results of the solidification phase diagram of the alloy obtained by adding different amounts of Zr in Example 10 of the present solution and Comparative Example 7 are shown. It is shown that excessive addition of Zr element causes Al3Zr particles to precipitate and coarsen before the aluminum liquid, which reduces the alloy performance and causes negative effects.

[0116] In summary, the present invention utilizes high-speed centrifugal shearing and iron removal technology of aluminum liquid to overcome the gravity field and temperature field effects in the melt and obtain an excellent purification effect. On the basis of preparing ingots with about 60% social waste aluminum addition, industrial-level homogenization, extrusion and heat treatment process technology for the precise control of β-Fe phase of recycled 6082 alloy has been developed, and the harmful Fe phase has been effectively harmlessly treated, so that the mechanical properties of the profile are significantly higher than those of similar products of the 6 series or even 7 series used by domestic and foreign OEMs, and the carbon emission factor of raw materials is reduced to below 10tCO2e / t, which lays a technical foundation for the future development of high-Fe tolerance deformation 6 series / 7 series recycled aluminum alloys that can be used in passenger cars, commercial vehicles, rail transit, high-speed rail and other fields.

[0117] Compared with the aluminum-iron alloy simulated scrap aluminum used in the laboratory stage, the final result of this scheme is a pilot test result. The scrap aluminum comes from a wide range of sources, not only contains more oil and impurities, but also contains a variety of trace elements, which will have a great impact on the microstructure of the alloy during the smelting process. For example, selenium will interfere with grain refinement. Even so, this scheme can still effectively improve the performance of 6082-T6 alloy (including yield strength, tensile strength and elongation) by optimizing the element composition, process steps and parameters, making it higher than the performance of mainstream 6082 products on the market, with unexpected technical effects.

[0118] The above is only an embodiment of the present invention, and the common knowledge such as the known specific technical solutions and / or characteristics in the solution is not described in detail here. It should be pointed out that for those skilled in the art, without departing from the technical solution of the present invention, several modifications and improvements can be made, which should also be regarded as the protection scope of the present invention, and these will not affect the effect of the implementation of the present invention and the practicality of the patent. The scope of protection required by this application shall be based on the content of its claims, and the specific implementation methods and other records in the specification can be used to interpret the content of the claims.

Claims

1. A low-carbon emission, high-strength aluminum alloy profile for transportation vehicles, characterized in that: The profile is 6082 alloy, including the following raw materials in percentage by mass: 58-60wt% of scrap aluminum, 0.7-1.3wt% of Si, 0.1-0.5wt% of Fe, 0-0.1wt% of Cu, 0.4-1wt% of Mn, 0.6-1.2wt% of Mg, 0-0.15wt% of Cr, 0-0.25wt% of Zn, 0.02-0.1wt% of Ti, 0.02-0.05wt% of Zr, and the remainder is aluminum ingots and impurities with a content of less than 0.05wt%.

2. The low carbon emission and high strength aluminum alloy profile for transportation vehicles according to claim 1, characterized in that: The Mg content is 0.7-1.0 wt%, and the Si content is 0.9-1.15 wt%.

3. The low carbon emission and high strength aluminum alloy profile for transportation vehicles according to claim 2, characterized in that: The Mn content is 0.6-0.65wt%, and the total amount of Mn and Cr is 0.7-0.8wt%.

4. The low carbon emission and high strength aluminum alloy profile for transportation vehicles according to claim 3, characterized in that: The 6082 alloy profile has a tensile strength of ≥320 MPa, a yield strength of ≥300 MPa, and an elongation of ≥8%.

5. A process for preparing a low-carbon emission high-strength aluminum alloy profile for a traffic vehicle according to any one of claims 1 to 4, characterized in that: The steps include: Step 1: Prepare the raw materials: prepare the raw materials according to the above ratio; Step 2, melting and casting treatment: the raw materials prepared above are put into a smelting furnace, the raw materials are melted in the smelting furnace, the alloy composition is adjusted, the high-purity argon gas in the furnace is refined without flux, and the raw materials are left to stand, and the double-rotor degassing furnace outside the furnace is degassed, and the 50ppi single-stage plate filter is purified, and the purified aluminum melt is cast into a recycled aluminum ingot by a semi-continuous casting equipment; Step 3: homogenization treatment: subjecting the ingot obtained in step 2 to a two-stage homogenization treatment to obtain an ingot; Step 4: extrusion treatment: extruding the ingot obtained in step 3 to obtain a profile; Step 5: straightening the profile obtained in step 4; Step 6: Solution treatment: subject the profile obtained in step 5 to solution treatment, and then perform water quenching; Step 7: Aging treatment: The profile obtained in step 6 is subjected to aging treatment to obtain a finished profile.

6. The process for preparing a low-carbon emission high-strength aluminum alloy profile for transportation vehicles according to claim 5, characterized in that: In step three, the two-stage homogenization treatment includes: primary homogenization, controlling the heating temperature to 440-460° C., and keeping the temperature for 4-6 hours; secondary homogenization, controlling the heating temperature to 550-570° C., and keeping the temperature for 13-17 hours.

7. The process for preparing a low-carbon emission high-strength aluminum alloy profile for transportation vehicles according to claim 6, characterized in that: In step 4, the extrusion process is to heat the ingot to a temperature of 490-530° C., a mold temperature of 460-500° C., an extrusion barrel temperature of 430-470° C., and an extrusion speed of 1-3 mm / s to obtain a profile.

8. The process for preparing a low-carbon emission high-strength aluminum alloy profile for transportation vehicles according to claim 7, characterized in that: In step six, the solution treatment is carried out at a temperature of 545 to 565° C. for 30 to 60 minutes.

9. The process for preparing a low-carbon emission high-strength aluminum alloy profile for transportation vehicles according to claim 8, characterized in that: In step seven, the aging treatment is to transfer the water-quenched profile to a temperature of 160-180° C. within 3 hours and keep it at that temperature for 7-9 hours.

Citation Information

Patent Citations

  • Aluminum alloy material, preparation method thereof and automobile high-strength seamless tube

    CN118166243A

  • High-strength regenerated aluminum alloy profile for automobile anti-collision beam and preparation process of high-strength regenerated aluminum alloy profile

    CN119101836A